(untitled) (Journal of Social Sciences Review, 2021)
The study’s goal was to examine secondary school teachers’ classroom management methods. Findings from this research will help secondary school instructors improve their classroom management, as well as identifying and resolving difficulties in the classroom management of secondary school teachers. There were 5623 male secondary school teachers in Swat who participated in the survey. To conduct the study, the researchers picked 100 instructors at random using basic random selection and then created a questionnaire to gather data from them. Researchers used self-administered surveys to collect the information, which was then evaluated using frequency, percentages, and the Chi-square test, among other methods. Using body language to curb misbehaviour in their classrooms was shown to be a classroom management strategy used by instructors in their classrooms, according to a research. Approaches for successful classroom management were discovered, including interactive discussion, rule-making in cooperation with students, allocating responsibilities to students, and providing a pleasurable atmosphere in courses for students to form rapport. Keywords:classroom management, district Swat, practices, secondary schools teachers